Oral Hydration Before and After Hip Replacement: The Notion Behind Every Action. (4th November 2022) - Briguglio, Matteo; Wainwright, Thomas W; Crespi, Tiziano; Southern, Kate; Mangiavini, Laura; Craig, James; Middleton, Rob G
Introduction: Even though nearly 20 patients undergo hip replacement every hour just in Italy and the United Kingdom, it is unclear what are the most appropriate oral hydration practices that patients should follow before and after surgery. Improper administration can cause postoperative fluid disturbances or exacerbate pre-existing conditions, which are not an uncommon find in older subjects. Significance: Considering that the number of hip operations is expected to increase in the next years as well as the age of patients, it is important to recall the notions behind water balance, especially in light of modern surgical and anesthetic practices. This technical perspective discusses the perioperative changes in the hydration status that occur during hip replacement and provides the concepts that help clinicians to better manage how much water the patient can drink. Results: The points of view of the surgeon, the anesthetist, and the nurse are offered together with the description of mineral waters intended for human consumption. Before surgery, water should be always preferred over caffeinated, sugar-sweetened, and alcoholic beverages. The drinking requirements on the day of surgery should consider the water output from urine, feces, respiration, exudation, and bleeding along with the water input from metabolic production and intravenous administration of fluids and medications. Healthy eating habits provide water and should be promoted before and after surgery. Conclusions: The judgment on which is the most appropriate approach to oral hydration practices must be the responsibility of the multidisciplinary perioperative team. Nevertheless, it is reasonable to argue that, in the presence of a patient with no relevant illness and who follows a healthy diet, it is more appropriate to stay closer to dehydration than liberalizing water intake both prior to surgery and in the early postoperative hours until the resumption of normal physiological functions.